Risk factors for medial and lateral compartment osteoarthritis of the knee: a cross-sectional analysis - Sultan, Mohammad Imtiaz; Saiful Arif, M.; Dey, Protyay; Deb, Aparna; Islam, Mohammed Taherul; Bhattacharjee, Ananya; Toufiqul Islam, M.; Jaber Abedin, M.; Chowdhery, Mohammad Kafil Uddin; Salman Ibna Zaman, M.; Saha, Mrinal (International Journal of Research in Medical Sciences, 2026)
Background: Knee osteoarthritis (OA) is a leading cause of disability among older adults worldwide. Compartment-specific involvement of the knee joint, particularly medial and lateral compartments, may be influenced by distinct biomechanical and demographic risk factors. Objective of the study was to assess the socio-demographic, radiographic, and biomechanical risk factors associated with medial and lateral compartment knee osteoarthritis among adult patients. Methods: A hospital-based cross-sectional study was conducted among 96 patients diagnosed with knee osteoarthritis. Socio-demographic data, clinical history, and radiographic findings were collected. Radiographic severity was assessed using Kellgren–Lawrence and Ahlback grading systems. Univariate and multivariate logistic regression analyses were performed to identify risk factors for compartment-specific osteoarthritis. Results: The mean age of participants was 59.59±8 years, with 86.5% aged above 50 years. Medial compartment involvement showed higher frequencies of osteophyte formation (86.5%), joint space narrowing (66.7%), and advanced Kellgren–Lawrence grades. Male sex (adjusted OR=3.09; p=0.031) was an independent predictor of medial compartment OA, while male sex demonstrated an inverse association with lateral compartment OA (adjusted OR=0.38; p=0.038). Conclusions: Medial compartment knee osteoarthritis was more prevalent and severe than lateral compartment involvement. Sex and knee alignment played significant roles in compartment-specific disease patterns. These findings highlight the need for targeted preventive and therapeutic strategies.